Cohort study exploring the association of cerebrospinal fluid metalloprotease levels and Microbiological characteristics to cerebral vasculitis complication in Pneumococcal meningitis - Lluïsa Guillem; Pedro Alia-Ramos; Aida Gonzalez-Diaz; Carmen Ardanuy; Lucia Boix-Palop; Eva Van den Eynde; Carmen Cabellos (Scientific Reports)
Abstract Cerebrovascular complications are frequent in pneumococcal meningitis and are associated with poor functional outcomes. Among these complications, the incidence of cerebral vasculitis (CV) has been increasingly reported, but neither its pathogenesis nor its relationship with cortisone treatment have been conclusively established. We wanted to describe cerebrospinal fluid (CSF) metalloprotease (MMP) levels, which are linked to cerebral damage and vasculitis (MMP-2, MMP-9, and the antagonist TIMP-1), and differences in microbiological serotypes or virulence factors that could be associated to the development of this complication. A prospective multicenter cohort study was performed from January 2019 to August 2022. All adult patients diagnosed with pneumococcal meningitis and for whom CSF samples from the initial lumbar puncture were available were included and followed up for six months after discharge. Streptococcus pneumoniae strains isolated from CSF or blood were assessed including whole genome sequencing and CSF levels of MMP-2, MMP-9, and TIMP-1 were measured. CV developed in three of 21 patients (14.3%). The serotypes of those who developed CV were 3, 9 N, and 35 F, with no microbiological differences with respect to the non-CV group. The CV group had higher CSF levels of MMP-9 (13.2 vs. 9.8 ng/L) and TIMP-1 (699 vs. 318 ng/L), but lower CSF levels of MMP-2 (5689 vs. 10,484 ng/L) compared with the non-CV group. Although no patients with CV died, they had worse clinical outcomes than the non-CV group. CV is a frequent complication of pneumococcal meningitis that may be associated with worse outcomes. No differences in microbiological serotypes or virulence factors were detected. Further analyses should be carried out to confirm whether CSF MMP levels may be markers of CV development.